2014
DOI: 10.3324/haematol.2013.096107
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic lymphocytic leukemia

Abstract: In the last decade, the management of chronic lymphocytic leukemia has undergone profound changes that have been driven by an improved understanding of the biology of the disease and the approval of several new drugs. Moreover, many novel drugs are currently under evaluation for rapid approval or have been approved by regulatory agencies, further broadening the available therapeutic armamentarium for patients with chronic lymphocytic leukemia. The use of novel biological and genetic parameters combined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…Moreover, there are new data impacting on the therapeutic choices: TP53 (or dysfunction); IGHV mutational status, serum B2 microglobulin, age and clinical stage (Rai/Binet); with these data, five risk groups have been calculated with SG, at five years, from 93.2% to 23.3%. Even with this information, CFR treatment, as used in this treatment, remains the first-line treatment [13,[39][40][41]. It is acceptable to use other combined anti CD20 with chemotherapy, instead of rituximab, with apparent advantages (obinotuzumab/chlorambucil) [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are new data impacting on the therapeutic choices: TP53 (or dysfunction); IGHV mutational status, serum B2 microglobulin, age and clinical stage (Rai/Binet); with these data, five risk groups have been calculated with SG, at five years, from 93.2% to 23.3%. Even with this information, CFR treatment, as used in this treatment, remains the first-line treatment [13,[39][40][41]. It is acceptable to use other combined anti CD20 with chemotherapy, instead of rituximab, with apparent advantages (obinotuzumab/chlorambucil) [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Ghia et al showed that the presence of NOTCH1 mutation correlated with resistance to treatment and with the risk of transformation into Richter syndrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…Two such therapeutic antibodies, ofatumumab (Arzerra) and rituximab (Rituxan), were approved by the FDA in October 2009 and February 2010, respectively. Although these two agents, when used in combination with traditional chemotherapies, significantly increase survival for many patients (85), a substantial number of patients have disease that does not respond to initial treatment or eventually becomes resistant to it (85,86). As a result, researchers began working to develop more effective CD20-targeted therapeutic antibodies.…”
Section: High-risk High-reward Preventionmentioning
confidence: 99%